Bag-1 stimulates Bad phosphorylation through activation of Akt and Raf kinases to mediate cell survival in breast cancer - Kizilboga, Tugba; Baskale, Emine Arzu; Yildiz, Jale; Akcay, Izzet Mehmet; Zemheri, Ebru; Can, Nisan Denizce; Ozden, Can; Demir, Salih; Ezberci, Fikret; Dinler-Doganay, Gizem (Springer Science and Business Media LLC, 2019)
Abstract Background Bag-1 (Bcl-2-associated athanogene) is a multifunctional anti-apoptotic protein frequently overexpressed in cancer. Bag-1 interacts with a variety of cellular targets including Hsp70/Hsc70 chaperones, Bcl-2, nuclear hormone receptors, Akt and Raf kinases. In this study, we investigated in detail the effects of Bag-1 on major cell survival pathways associated with breast cancer. Methods Using immunoblot analysis, we examined Bag-1 expression profiles in tumor and normal tissues of breast cancer patients with different receptor status. We investigated the effects of Bag-1 on cell proliferation, apoptosis, Akt and Raf kinase pathways, and Bad phosphorylation by implementing ectopic expression or knockdown of Bag-1 in MCF-7, BT-474, MDA-MB-231 and MCF-10A breast cell lines. We also tested these in tumor and normal tissues from breast cancer patients. We investigated the interactions between Bag-1, Akt and Raf kinases in cell lines and tumor tissues by co-immunoprecipitation, and their subcellular localization by immunocytochemistry and immunohistochemistry. Results We observed that Bag-1 is overexpressed in breast tumors in all molecular subtypes, i.e., regardless of their ER, PR and Her2 expression profile. Ectopic expression of Bag-1 in breast cancer cell lines results in the activation of B-Raf, C-Raf and Akt kinases, which are also upregulated in breast tumors. Bag-1 forms complexes with B-Raf, C-Raf and Akt in breast cancer cells, enhancing their phosphorylation and activation, and ultimately leading to phosphorylation of the pro-apoptotic Bad protein at Ser112 and Ser136. This causes Bad’s re-localization to the nucleus, and inhibits apoptosis in favor of cell survival. Conclusions Overall, Bad inhibition by Bag-1 through activation of Raf and Akt kinases is an effective survival and growth strategy exploited by breast cancer cells. Therefore, targeting the molecular interactions between Bag-1 and these kinases might prove an effective anticancer therapy.
Keywords: Cell Survival; Apoptosis; Breast Neoplasms; Breast cancer; Cell Line, Tumor; Humans; Phosphorylation; Bag-1; RC254-282; Cell Proliferation; Akt; Bad phosphorylation; Neoplasms. Tumors. Oncology. Including cancer and carcinogens; Middle Aged; Up-Regulation; DNA-Binding Proteins; Gene Expression Regulation, Neoplastic; Raf kinase; Female; bcl-Associated Death Protein; raf Kinases; Protein Processing, Post-Translational; Proto-Oncogene Proteins c-akt; Research Article; Signal Transduction; Transcription Factors